2019
DOI: 10.1111/iju.13960
|View full text |Cite
|
Sign up to set email alerts
|

Selective culture of Escherichia coli to prevent infective complications of transrectal ultrasound‐guided prostate biopsy: Clinical efficacy and analysis of characteristics of quinolone‐resistant Escherichia coli

Abstract: Objectives To evaluate a regimen of targeted prophylaxis using rectal swab culture in patients undergoing transrectal ultrasound‐guided prostate biopsy, and to investigate the characteristics of isolated fluoroquinolone‐resistant Escherichia coli. Methods A prospective study was carried out from June 2013 through December 2014. Rectal swabs were cultured on agar plates containing either 2 μg/mL levofloxacin or 1 μg/mL sitafloxacin before transrectal ultrasound‐guided prostate biopsy. Patients with susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Hiyama et al (2019) showed that a combination of empirical and target prophylaxis, guided by pre-biopsy rectal swabs, could be a good strategy to decrease the number of biopsy complications. 23 A similar rate of post-biopsy infections was shown in our study. Resistance to antibiotics on fecal microbiota has not been individualized as a possible risk factor for post-biopsy complications, differently than reported in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hiyama et al (2019) showed that a combination of empirical and target prophylaxis, guided by pre-biopsy rectal swabs, could be a good strategy to decrease the number of biopsy complications. 23 A similar rate of post-biopsy infections was shown in our study. Resistance to antibiotics on fecal microbiota has not been individualized as a possible risk factor for post-biopsy complications, differently than reported in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…These results are comparable to the contemporary series, including those under the target and empirical prophylaxis protocols. 6,911,2123 Since no resistance to ciprofloxacin/gentamicin neither to ciprofloxacin/ceftriaxone combination has been identified in our cohort, we believe that is acceptable to extrapolate our findings to compare our results with those from target prophylaxis. Hiyama et al (2019) showed that a combination of empirical and target prophylaxis, guided by pre-biopsy rectal swabs, could be a good strategy to decrease the number of biopsy complications.…”
Section: Discussionmentioning
confidence: 85%
“…Although several studies have examined the effectiveness of pre-biopsy rectal swab culture, 11,[16][17][18] only a few studies have explored the clinical utility of urine culture before TR-PB. 14,15 Bruyère et al reported that 3.4% (12 of 353 patients who received transrectal needle biopsy) had positive pre-biopsy urine culture (>1×10 5 CFU/mL) 48-72 h before PB, and only 1.1% of patients with negative prebiopsy urine culture developed infectious complications following PB.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative use of selective media allows the isolation and analysis of these strains, consequently, more information can be collected and thus, preventing complications associated with invasive procedures such as prostate biopsy. The clinical efficacy and analysis of characteristics of quinolone‐resistant E. coli using selective culture were determined by Hiyama et al 59 . The results of the analysis of 420 patients showed 75 (17.8%) had FQ‐resistant E. coli , although none of the carriers presented any infectious complications related to resistant pathogens using targeted antimicrobial prophylaxis, they suggested that a pre‐operative selective media method might prevent infectious complications after prostate biopsy.…”
Section: Screening Cultures Using Selective Mediamentioning
confidence: 99%